Los derechos humanos en ecuador durante la crisis sanitaria derivada del COVID-19 - Cruz-Piza, Iyo Alexis; Salcedo-Valverde, Neiva; Valencia-Vera, Humberto; Ortíz-Quiñonez, Galo (IUSTITIA SOCIALIS, 2021)
Los derechos humanos en ecuador durante la crisis sanitaria derivada del COVID-19